Frequency of Bednar’s Aphthae in Neonates in a Tertiary Care Hospital in Karachi, Pakistan - Hussain, Madiha; Mallick, Shabbir Ahmed; Haroon, Misbah; Naz, Rubab (Biological and Clinical Sciences Research Journal, 2025)
Bednar’s aphthae are benign ulcerative lesions typically observed on the hard palate of neonates, often resulting from mechanical trauma during feeding. Despite being self-limiting, they are underdiagnosed and underreported, particularly in developing countries like Pakistan. Objective: This study aimed to determine the frequency of Bednar’s aphthae and explore associated risk factors among neonates in a tertiary care setting in Karachi. Methods: A cross-sectional study was conducted at the Pediatric Medicine OPD of Liaquat National Hospital, Karachi, from June 2024 to December 2024. A total of 105 neonates aged less than one month were enrolled. Data on demographics, feeding method, delivery mode, and socioeconomic status were collected through a structured Performa. Results: The frequency of Bednar’s aphthae was found to be 13.3% (14 out of 105 neonates). A significant association was observed between feeding method and presence of aphthae (p = 0.001), with 71.4% of cases occurring in bottle-fed infants. No statistically significant relationship was found with gender (p = 0.73), age group (p = 0.18), mode of delivery (p = 0.12), or socioeconomic status (p = 0.09). Conclusion: Bednar’s aphthae are not uncommon and are significantly associated with bottle feeding. Educating caregivers about proper feeding techniques and promoting breastfeeding could help prevent this condition. Early recognition can prevent misdiagnosis and unnecessary treatment. Further studies are warranted to explore broader risk factors and preventive strategies.